Variation in energetic balance among free-ranging polar bears during the spring mating and foraging season - Anthony M. Pagano; Stephen N. Atkinson; Louise C. Archer (Arctic Science)
Large carnivores are capable of consuming substantial biomasses that can significantly alter their body mass and condition over short periods. Here we examine the intra-seasonal variation of polar bear (Ursus maritimus Phipps, 1774) body mass, energy intake, and condition in the spring from two subpopulations. We evaluate the biological and temporal factors that may have driven changes in body mass of 31 individuals captured and recaptured over 2–39 days and assess whether these changes influenced their estimated condition. Body mass changed by –61 to 33 kg ([Formula: see text] = –2 kg) with bears exhibiting increases in mass with increasing age and decreases with greater initial mass. On average, estimated intake was 57 MJ/day. Estimated daily mass-specific body mass changes exhibited greater variation relative to previous measures in polar bears or brown bears (U. arctos Linnaeus, 1758). Yet, across all bears, measures of condition remained similar between captures. The marked variation in mass gains or losses highlights the varying behavioral and physiological limitations that influence foraging success within this apex carnivore during a season when two key life history events converge wherein feeding is often reduced during mating activities despite the importance of the spring hyperphagia period to long-term energy balance.